2017
DOI: 10.1111/1475-4932.12328
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Immigration to Australia and the Labour Market Outcomes of Australian‐Born Workers

Abstract: We examine the relationship between immigration to Australia and the labour market outcomes of Australian‐born workers. We use immigrant supply changes in skill groups, defined by education and experience, to identify the impact of immigration on the labour market. We find that immigration flows into those skill groups that have the highest earnings and lowest unemployment. Once we control for the impact of experience and education on labour market outcomes, we find almost no evidence that immigration harms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…This overall similarity of labour market outcomes occurs despite Australia's immigrants having higher levels of educational attainment than their Australian‐born counterparts of the same age, and also reflects immigrants' lower returns to education in terms of labour market outcomes (Kler ; Piracha, Tani and Vadean ; De Alwis and Parr ). Similarly, the model assumes neutrality of the effects of net immigration on employment rates of the Australian‐born, which is consistent with recent evidence (Productivity Commission ; Breunig, Deutscher and To ).…”
Section: Methodssupporting
confidence: 84%
“…This overall similarity of labour market outcomes occurs despite Australia's immigrants having higher levels of educational attainment than their Australian‐born counterparts of the same age, and also reflects immigrants' lower returns to education in terms of labour market outcomes (Kler ; Piracha, Tani and Vadean ; De Alwis and Parr ). Similarly, the model assumes neutrality of the effects of net immigration on employment rates of the Australian‐born, which is consistent with recent evidence (Productivity Commission ; Breunig, Deutscher and To ).…”
Section: Methodssupporting
confidence: 84%
“…Another set of skill‐cell studies finds no detrimental impact of immigration on the wages and employment of competing native workers, for example, Breunig et al . () for Australia. For Germany, D'Amuri et al .…”
Section: Empirical Evidencementioning
confidence: 92%
“…The studies by Breunig et al . () for Australia; Winter‐Ebmer and Zweimüller () for Austria; Pischke and Velling () for Germany; Dustmann et al . () for Great Britain; Zorlu and Hartog () for the Netherlands, Norway, and the United Kingdom; and Basso and Peri () for the United States detect no negative or positive impact of immigration at the local level.…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In the long run, the results indicated that immigration negatively affected the rate of unemployment of the host countries. Breunig, Deutscher, and To (2017) examined the effect of immigration on the labour market outcomes of Australian workers using the national labour market approach by dividing immigrants into educational groups and experience groups. Their main findings concluded that immigration flows into skill groups where wages and employment are high; however, there was no evidence that labour market outcomes for individuals born in Australia were negatively affected by immigration.…”
Section: Immigration and Unemploymentmentioning
confidence: 99%